Synthesis of a novel flame retardant containing phosphorus, nitrogen and boron and its application in flame-retardant epoxy resin - Yang, Shuang; Zhang, Qiaoxin; Hu, Yefa (Polymer degradation and stability, 2016)
A novel halogen-free flame retardant (DTB) containing phosphorus, nitrogen and boron was successfully synthesized. The chemical structure of DTB was characterized by Fourier transform infrared spectroscopy (FTIR), 1H and 31P nuclear magnetic resonance (NMR). DTB was then blended with diglycidyl ether of bisphenol-A (DGEBA) to prepare flame-retardant epoxy resins. Thermal properties, flame retardancy and combustion behavior of the cured EP thermosets were investigated by thermogravimetric analysis (TGA), limited oxygen index (LOI) measurement, UL94 vertical burning test and cone calorimeter test. The results indicated that DTB significantly improved the flame retardancy as well as smoke inhibition performance of EP/DTB thermosets. Compared with the neat EP thermoset, the LOI of EP/DTB-3 thermoset was increased to 35.6% and the sample reached UL94 V-0 rating; the average of heat release rate (av-HRR), total heat release (THR) and total smoke production (TSP) of EP/DTB-3 thermoset were decreased by 33.3%, 33.0% and 35.5%, respectively. TGA results indicated that the char yields of EP/DTB thermosets were increased by 45.1–72.8% compared with that of the neat EP thermoset. The FTIR, SEM-EDX and Py-GC/MS results indicated that DTB contributed to form intumescent and glassy char layers and decomposed to generate free radicals with quenching effect. DTB was effective radical trapper as well as efficient charring agent for epoxy resin and exerted flame-retardant effect in gaseous and condensed phases simultaneously.